Petrography of the Nahan Formation Exposed in the Type Area Nahan and Adjoining Regions in Northwestern Himalaya, India: A Petrographical Analysis of the Middle Miocene Nahan Formation in Northwestern Himalaya, India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The petrography of the Middle Miocene Nahan Formation of the type area, northwestern Himalaya, India has been analyzed to understand the paleoclimatic and paleotectonic conditions in the frontal Himalayan terrain. 250 thin sections of rocks collected from Lower Siwalik Nahan Formation exposed in the selected and measured three sections (Shambhuwala – Nahan section, Renuka – Nahan section and Sataun – Rajban section) of the northwestern Himalaya were subjected to petrographical and mineralogical investigations. Various petrological units distinguished in the Lower Siwalik Formation include lithic arenite ferruginous cement, quartz wacke, lithic arenite siliceous cement, quartz arenite, siltstone/clays/shales. The detrital grains are angular to subangular and have moderate sorting.